What Factors Determine Disclosure of Suicide Ideation in Adults 60 and Older to a Treatment Provider?. Issue 3 (3rd February 2014) - Cukrowicz, Kelly C.; Duberstein, Paul R.; Vannoy, Steven D.; Lin, Elizabeth H.; Unützer, Jürgen
<x xml:space="preserve">Abstract</x> Correlates of patient disclosure of suicide ideation to a primary care or mental health provider were identified. Secondary analyses of IMPACT trial data were conducted. Of the 107 patients 60 years of age or older who endorsed thoughts of ending their life at least "a little bit" during the past month, 53 indicated they had disclosed these thoughts to a mental health or primary care provider during this period. Multiple logistic regression was used to identify predictors of disclosure to a provider. Significant predictors included poorer quality of life and prior mental health specialty treatment. Among participants endorsing thoughts of suicide, the likelihood of disclosing these thoughts to a provider was 2.96 times higher if they had a prior history of mental health specialty treatment and 1.56 times higher for every one‐unit decrease in quality of life. Variation in disclosure of thoughts of suicide to a mental health or primary care provider depends, in part, on patient characteristics. Although the provision of evidence‐based suicide risk assessment and guidelines could minimize unwanted variation and enhance disclosure, efforts to routinize the process of suicide risk assessment should also consider effective ways to lessen potential unintended consequences.